2012
DOI: 10.1093/jat/bks040
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Chloralose in a Fatal Intoxication

Abstract: Chloralose (alpha-chloralose) is a poisonous substance currently used as a rodenticide or avicide. It has primarily been used in Europe since 1893 as a human and veterinary hypnotic agent. Chloralose is a central nervous system depressant also acting as a stimulant on spinal reflexes. In the present case, a 24-year-old man was found dead in his bedroom near vomit residues. Several items were seized from the scene, including an empty bottle of Murex 50 g (α-chloralose), sold in Italy as rodenticide. Postmortem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In people, both accidental and intentional AC poisoning with either fatal or non‐fatal outcome have been reported (Thomas and others 1988, Federici and others 2006, Gerace and others 2012). Typical clinical features included coma and generalised convulsions (Thomas and others 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In people, both accidental and intentional AC poisoning with either fatal or non‐fatal outcome have been reported (Thomas and others 1988, Federici and others 2006, Gerace and others 2012). Typical clinical features included coma and generalised convulsions (Thomas and others 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, these substances are also dangerous for domestic animals such as cats and dogs, as secondary poisoning might occur when a predator eats a poisoned rodent. Additionally, since human poisoning with rodenticides also occurs on a regular basis, a reliable and convenient identification of relevant substances in forensic toxicological laboratories is important 1–5 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since human poisoning with rodenticides also occurs on a regular basis, a reliable and convenient identification of relevant substances in forensic toxicological laboratories is important. [1][2][3][4][5] There are several classes of rodenticides. Based on our own searches, it was found that different coumarin derivatives (brodifacoum, bromadiolone, coumatetralyl, difenacoum, and warfarin) as anticoagulants and α-chloralose with anesthetic and sedative properties are readily commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…AC is no longer used clinically either in veterinary or in human clinical practice. It is however still used as a rodenticide and as an anesthetic agent to sedate laboratory animals ( 3 , 5 , 6 , 8 , 9 ), and peer-reviewed case reports summarizing the clinical symptoms of AC poisoning in humans and several animal species, including human cases with lethal outcomes, are available ( 3–6 , 9–11 ). Together, the data in such reports describe a range of neurological symptoms similar to what are described in older experimental studies evaluating the toxic effects of AC.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter et al. applied LC–MS-MS to analyze stomach content and tissue samples from poisoned birds of prey ( 16 ), and Gerace and co-workers studied the distribution of AC in the human body in a postmortem investigation of a fatal AC intoxication case ( 6 ), and Leporati et al. analyzed rodenticides in human hair ( 17 ).…”
Section: Introductionmentioning
confidence: 99%